(untitled) (Third Sector Social Economic Review, 2022)
Although it is generally accepted that the Ottoman economy declined in the XIXth century, contrary views are also put forward. In this study, the structural situation of the XIXth century Bursa silk sector is examined within the framework of economic mindset principles. A method is followed by comparing the information gathered from secondary sources regarding the sector, taking into account the structural changes. The main result obtained is that the Bursa silk sector underwent a structural transformation in the XIXth century, depending on the entry of European products into the Ottoman market. That is to say, the sector had undergone a structural transformation in the form of specialization in raw material production. In this process, the manufactures were put into operation and the capitalist production stage was passed. On the other hand, although it does not have an absolute validity, the structural transformation in the form of specialization in raw material production in the sector can be considered as an example of ""deindustrialization"" as a result of being included in the international division of labor. As a matter of fact, the continuation of the production with traditional methods (hand looms) in accordance with local tastes shows that our deduction of deindustrialization is not absolute: Until the XXth century, poşu, keyfiye, scarves, krep, kutnu, abani and old velvets continued to be woven on hand looms. When the above mentioned results are evaluated within the framework of mindset principles; first of all, the abolition of guilds throughout the country means the abandonment of both iaşe and traditionalism. Secondly, the continuation of the taxation of the sector, although it has not been examined in order not to exceed the limitation of the study, can be accepted as an application of the principle of fiscalism. In fact, the disappearance of mindset principles, except for fiscalism, can be considered as an expression of a development in the direction of capitalism.